Carbon Accumulation in Soils During Reforestation — The Australian Experience After Bauxite Mining - Tibbett, M (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
Soil is the primary store of terrestrial carbon, and is seriously disturbed by mining activities. Soil carbon exists in various forms that are functionally different and have contrasting residence times as part of the soil organic matter store. Here I explore the nature of soil carbon, from surface litter stocks to humified fractions, as measured from various rehabilitated (reforested) bauxite mined land across Australia. Litter in rehabilitated forests tends to accumulate to higher masses than in the surrounding native forests. This may simply be a function of extra litterfall during forest regrowth and higher stem densities than in the natural forests, or of lower decomposition rates. The higher litter stocks in restored forests are sometimes reflected in a higher carbon concentration in the mineral soil. However, the type of carbon that accumulates in the mineral soils after bauxite mining may be primarily of particulate organic form that is not stable in the long- term and may readily mineralize to CO2. Further research is required to establish the stability of carbon in the soils of rehabilitated forests and woodlands compared to their natural systems and the implication for carbon accounting and climate change.